Organochlorine pesticides and epigenetic alterations in thyroid tumors - Salimi, Fouzieh; Asadikaram, Gholamreza; Ashrafi, Mohammad Reza; Zeynali Nejad, Hamid; Abolhassani, Moslem; Abbasi-Jorjandi, Mojtaba; Sanjari, Mojgan (Frontiers in Endocrinology, 2023)
Abstract Purpose: Cancer incidence depends on various factors e.g., pesticide exposures which cause epigenetic alterations. The present research aimed to investigate the organochlorine pesticides (OCPs) impacts on promoter methylation of three tumor-suppressor genes and four histone modifications in thyroid nodules in 61 Papillary thyroid carcinoma (PTC) and 70 benign thyroid nodules (BTN) patients. Methods: OCPs were measured by Gas chromatography. To identify promoter methylation of TSHR, ATM, and P16 genes, the nested-methylation-specific PCR (MSP) was utilized, and histone lysine acetylation (H3K9, H4K16, and H3K18) and lysine methylation (H4K20) were detected by performing western blot analysis. Results: Further TSHR methylation and less P16 methylation were observed in PTC than in BTN. No substantial difference was detected for ATM methylation between PTC and BTN groups. Also, OCP dramatically increased the odds ratio of TSHR (OR=3.98, P=0.001) and P16 (OR=5.65, P<0.001) methylation while confounding variables reduced the chances of ATM methylation arising from 2,4-DDE and 4,4-DDT influence. Hypomethylation of H4K20 and hypo-acetylation of H3K9, H4K16, and H3K18 (P<0.001) were observed in PTC samples than BTN. Furthermore, OCPs substantially decreased the odds ratio of H3K9 (OR=3.68, P<0.001) and H4K16 (OR=6.03, P<0.001) acetylation. Conclusion: The current research indicated that OCPs could contribute to PTC progression by TSHR promoter hypermethylation and decreased acetylation of H3K9 and H4K16. In addition, in PTC patients, assessing TSHR promoter methylation and acetylation of H3K9 and H4K16 could have predictive values.